2022
DOI: 10.1039/d2ta00941b
|View full text |Cite
|
Sign up to set email alerts
|

Design of 3d transition metal anchored B5N3 catalysts for electrochemical CO2 reduction to methane

Abstract: Carbon dioxide (CO2) reduction to value-added fuels and chemicals by making full use of the electricity generated from clean energy is promising to address environmental pollution and the energy crisis....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 77 publications
0
21
0
Order By: Relevance
“…2 Of all the feasible routes, electrochemical reduction of CO 2 into various types of fuels via renewable electricity is the most promising solution. [3][4][5][6] Currently, CO 2 can be converted into many types of value-added fuels or chemicals, such as carbon monoxide (CO), 7 methanol (CH 3 OH), 8 formic acid (HCOOH), 9 ethylene (C 2 H 4 ), 10,11 ethanol, 12 methane (CH 4 ), 13 and urea (CH 4 N 2 O), 14 depending on the surface properties of the electrocatalysts. 15 In all products, CO is available over a wide range of inexpensive electrocatalysts, and it is also economically viable as a feedstock for subsequent thermochemical reactions, 16 for instance, the very important Fischer-Tropsch synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…2 Of all the feasible routes, electrochemical reduction of CO 2 into various types of fuels via renewable electricity is the most promising solution. [3][4][5][6] Currently, CO 2 can be converted into many types of value-added fuels or chemicals, such as carbon monoxide (CO), 7 methanol (CH 3 OH), 8 formic acid (HCOOH), 9 ethylene (C 2 H 4 ), 10,11 ethanol, 12 methane (CH 4 ), 13 and urea (CH 4 N 2 O), 14 depending on the surface properties of the electrocatalysts. 15 In all products, CO is available over a wide range of inexpensive electrocatalysts, and it is also economically viable as a feedstock for subsequent thermochemical reactions, 16 for instance, the very important Fischer-Tropsch synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…9 Moreover, CO 2 RR can be carried out under mild conditions, and the required electrical energy can be obtained from renewable energy sources. Although state-of-the-art electrocatalysts electively produce various C1 products (carbon monoxide, 10,11 formic acid, 12,13 methane, 14,15 and methanol 16 ) and C2 products (ethylene 17 and ethanol 18 ) through different reaction pathways, it is challenging to further expand the range of products. The introduction of an N source as a reactant into CO 2 RR, in addition to CO 2 and H 2 O, to produce organo-nitrogen compounds (urea and ammoniate) is a highly efficient approach that can address both the concerns of environmental issues and energy crisis simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…During recent years, single-atom catalysts (SACs) have been used for removing atmospheric pollutants due to their promising catalytic activity and selectivity. [26][27][28] Many studies showed that graphene-based SACs doped with transition metals (TMs) can chemically adsorb Hg 0 . Liu et al 29 analyzed the adsorption of Hg 0 on pure, vacancy-defect, 30 and Aldoped graphene surfaces, and found that single-Al doped graphene showed the best adsorption performance on Hg 0 .…”
Section: Introductionmentioning
confidence: 99%